DEVELOPING AUTHENTIC READING MATERIAL FOR THE TENTH YEAR STUDENTS OF STATE VOCATIONAL HIGH SCHOOL 1 KUBUTAMBAHAN - Putu Yuli, Budiantari; Putu, Kerti Nitiasih; I Gede, Budasi (Jurnal Pendidikan Bahasa Inggris, 2013)
This study aimed at (i) developing authentic reading material for the tenth year students of Vocational high school based on the School Based Curriculum that meet the criteria of a good reading material, (ii) identifying the reading materials which have been used in SMK negeri 1 Kubutambahan, (iii) identifying the types of reading material which are needed to be developed fro the tenth year students of SMK Negeri 1 Kubutambahan, (iv) identifying the reading topics which were needed to be developed for the tenth year students of SMK Negeri 1 Kubutambahan, (v) developing reading activities that could be included and needed to be developed for the tenth year students of SMK Negeri 1 Kubutambahan. Â The data were gained using research instruments such as questionnaires, rubrics, and interview guides in order to find the compatibility of the existing materials and the developed materials with the syllabus and the criteria of good materials. Gall and Gall design model was employed as the present research procedures. The obtained data were quantitatively analyzed by using percentage of frequency. From the results, new materials were developed based on the requirements of syllabus analysis, criteria of good materials and good reading materials. After being developed, the materials were evaluated by experts. The results of the analysis were used as guideline for revising the developed materials. After being revised, the new materials were field-tested in the tenth year grade of SMK Negeri 1 Kubutambahan after conducting pre-test in order to identify the studentsâ prior knowledge. After field-test, post-test was conducted to identify whether or not the developed materials could improve the studentsâ reading comprehension. The next step was revising the results of the field test. After field-testing, the rubrics for analyzing the quality of developed materials were distributed to the teacher and the students. The obtained data were analyzed and categorized to ascertain rating scales. In conclusion, it was found that (i) the reading materials were developed based on the criteria of good materials, and the school-based curriculum and BSNP for the tenth year students of Vocational High School and considered as good reading materials, based on the criteria proposed by Tomlinson (1998, (ii) the existing materials in the English book used did not fully meet the requirements of the syllabus and curriculum, and categorized as average materials, (iii) authentic reading materials were the type of materials needed to be developed for the tenth year students of SMK Negeri 1 Kubutambahan, (iv) the reading topics which were needed to be developed were based on the SBC syllabus, (v) the reading activities that can be included and needed to be developed for the tenth year students of SMK Negeri 1 Kubutambahan were reading activities which based on the criteria proposed by Tomlinson (1998) and SBC. Keywords: material development, authentic reading materials